Liberalism and Value Pluralism. - Crowder, George (Political theory and contemporary politics., 2002)
Value pluralism is the idea, associated with the late Isaiah Berlin, that fundamental human values are irreducibly plural and incommensurable. Ends like liberty, equality and community are intrinsic goods which can neither be ranked in an absolute hierarchy nor translated into units of a common denominator. If that is true, how can we choose among such values when they come into conflict in particular cases? In particular, what reason is there to justify the value ranking characteristic of liberal democracy, favouring personal autonomy and toleration? Recent commentators have seen value plural.